IDENTIFIKASI PATOTIPE GLOBODERA ROSTOCHIENSIS MENGGUNAKAN KLON DIFERENSIAL - . Lisnawita; . Supramana; Gede Suastika (Universitas Lampung, 2013)
Identification of Globodera rostochiensis using differential clones. Potato cyst nematode, Globodera rostochiensis, is a relatively new pathogen in Indonesia that becomes a constraint to potato production. To manage the parasite effectively, it is very important to identify the pathotype of G. rostochiensis populations. Therefore, this research was carried out to identify G. rostochiensis pathotypes. Four G. rostochiensis samples, consisting of three samples from East Java and one sample from Central Java, were identified using a set of differential clones. The result showed that G. rostochiensis samples from East Java were new pathotype, whereas the sample from Central Java was Ro1 pathotype.